2002
DOI: 10.3171/jns.2002.97.1.0104
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic depolarization monitoring: evaluation of protein synthesis in the hippocampal CA1 after brief unilateral ischemia in a gerbil model

Abstract: In this study the authors demonstrate that monitoring of ischemic depolarization is a useful method to predict neuronal damage in the hippocampal CA1 in this model, and they identify subtle changes in protein synthesis after brief ischemia. Sublethal ischemia was divided into three categories by its depolarization period (< 90 seconds, 90-180 seconds, and > 180-210 seconds) with regard to changes in protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Second, it has been shown that cerebral ischemia causes long-lasting inhibition of protein synthesis despite recovery of energy metabolism (Olsson et al, 2003). This latter point was highlighted in a study showing that gerbils that underwent sublethal ischemia needed a 7-day recirculation period before protein synthesis in hippocampal neurons returned to a normal level (Sorimachi et al, 1999, 2002). Hence, we used a 7-day post-ischemia recovery period to ensure maturation of delayed neuronal death.…”
Section: Discussionmentioning
confidence: 97%
“…Second, it has been shown that cerebral ischemia causes long-lasting inhibition of protein synthesis despite recovery of energy metabolism (Olsson et al, 2003). This latter point was highlighted in a study showing that gerbils that underwent sublethal ischemia needed a 7-day recirculation period before protein synthesis in hippocampal neurons returned to a normal level (Sorimachi et al, 1999, 2002). Hence, we used a 7-day post-ischemia recovery period to ensure maturation of delayed neuronal death.…”
Section: Discussionmentioning
confidence: 97%
“…Core temperatures were recorded after 30 min and then every day until the mice were sacrificed 7 days later. This post-ischemic recovery period was chosen to ensure maturation of delayed neuronal death because it was previously shown in gerbils that 7 days was required for protein synthesis to return to normal levels (Sorimachi et al, 1999;Sorimachi et al, 2002).…”
Section: Global Ischemiamentioning
confidence: 99%
“…Thus, the use of inhibitors of protein synthesis as inducers of cell death allows the isolated analysis of the execution pathways of cell death. Furthermore, analysis of cell death induced by translation inhibitors may be of clinical relevance, because inhibition of protein synthesis occurs in neurons during ischemia, immediately upon reperfusion and persists particularly in regions known to suffer extensive cell death (55)(56)(57). It should be noted that, within the time frame examined in our model, cell death following inhibition of protein synthesis is restricted to a specific population of cells (39), and therefore does not represent a trivial metabolic effect.…”
Section: Caspase-9 Induces An Alternative Pathway Of Cell Death Inmentioning
confidence: 99%